Factors influencing Purchase Decisions on Somethinc Products - Mardah Pristy Andriyani Iskandar; Jenji Gunaedi Argo (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This research is a quantitative study using primary data sources and the authors use descriptive and inferential analysis techniques and SmartPLS (Partial Least Square) as a tool used in this study. The purpose of this study is to show whether the purchasing decision variables are influenced by the variables of product quality, brand image, and electronic word of mouth for Somethinc products. And the object of this research is 18 year old women who uses Somethinc products. The sample of data sources in this study was obtained by distributing it to 100 female respondents and the authors chose accidental sampling as the sampling technique used in this study. The results of data processing can be seen that: (1) purchasing decisions can be influenced by product quality (2) purchasing decisions can also be influenced by brand image (3) purchasing decisions can also be influenced by electronic word of mouth.